2021
DOI: 10.1177/19386400211058264
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Complications and Reoperations Between Open Reduction and Internal Fixation Versus Primary Arthrodesis Following Lisfranc Injury

Abstract: There is a lack of consensus in the literature regarding optimal treatment methods for Lisfranc injuries, and recent literature has emphasized the need to compare open reduction and internal fixation (ORIF) with primary arthrodesis (PA). The purpose of the current study is to compare reoperation and complication rates between ORIF and PA following Lisfranc injury in a private, outpatient, orthopaedic practice. A retrospective chart review was performed on patients undergoing operative intervention for Lisfranc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…1st cuneiform to 2nd metatarsal diastasis was the second most common diagnostic criteria in the anteroposterior view and was employed in eight studies [29,32,36,37,40,41,43,44]. Medial column alignment was reported in six studies [19,29,32,[40][41][42]. The eck sign was fully employed in three studies [17,20,22] but mixed in three more other studies [23,28,34], and the notch sign was employed in one study [24].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1st cuneiform to 2nd metatarsal diastasis was the second most common diagnostic criteria in the anteroposterior view and was employed in eight studies [29,32,36,37,40,41,43,44]. Medial column alignment was reported in six studies [19,29,32,[40][41][42]. The eck sign was fully employed in three studies [17,20,22] but mixed in three more other studies [23,28,34], and the notch sign was employed in one study [24].…”
Section: Resultsmentioning
confidence: 99%
“…Oblique View 3rd cuneiform to 3rd metatarsal [19,21,27,31,[42][43][44] and cuboid to 4th metatarsal subluxation [19,21,23,31,[42][43][44] were both the radiographic diagnostic criteria observed in the oblique view and employed in seven studies each.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One must use caution in interpreting these results as the study was severely underpowered with retention of only 32 of 60 patients needed to meet their predetermined benchmark for statistical power. Finally, So et al 40 reported that PA had a significantly longer time to weightbearing than ORIF. However, further analysis revealed that the difference was 0.7 days, which brings into question the clinical relevance of this finding.…”
Section: Fragility Analysis Of "Return To Function" Outcomesmentioning
confidence: 97%
“…In those patients treated with IF, 46% (n = 11) developed post-traumatic degenerative changes in the first TMTJ, but only 1 patient required secondary arthrodesis. So et al performed a retrospective study comparing complications and reoperation rates in 130 patients treated with IF and 66 patients treated with PA 85 . The reoperation rate was significantly higher in the fixation group (78% vs. 20%), but when hardware removal cases were excluded, the reoperation rates were comparable, as were the overall complication rates.…”
Section: Treatmentmentioning
confidence: 99%